The Cluster Approach for Developing Power Supply Systems in Uzbekistan’s Remote and Hard-to-Reach Territories - Olga V. Radionova; Rashid А. Sitdikov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the Republic of Uzbekistan is gradually developing remote and hard-to-reach territories that possess reserves of various natural resources. One of the main problems that needs to be addressed is the issue of sustainable energy supply (electrification) for such territories. The use of traditional methods, such as constructing power lines, developing energy infrastructure, etc., in remote areas requires significant costs that will pay off over many years. In the context of developing market relations in the energy sector, it is necessary to create conditions for attracting entrepreneurs and businessmen, securing investments, introducing new technologies, ensuring staffing, and so on. Such work on electrifying remote areas needs to begin in advance due to the long development periods of electrification processes. The electrification of remote areas should occur through alternative and renewable energy sources (АRES) and the utilization of local resources. Therefore, analyzing the effectiveness of electrification methods for remote areas and developing proposals for their implementation is relevant. This work proposes the consolidation of distributed energy facilities by creating virtual clusters as a tool to ensure the sustainable development of power supply systems in remote and hard-to-reach areas. Aim: to analyze and develop proposals for the clustering (consolidation) of small energy facilities in remote and hard-to-reach areas to create sustainable conditions for their operation. Methods: theoretical approaches to clustering small and medium-sized energy facilities, system analysis methods, and multi-criteria evaluations were used, along with consideration of ESG principles. Results: an analysis was conducted, and proposals were developed for the effective clustering of distributed energy facilities in remote territories, enabling their consolidation and thereby ensuring the sustainable functioning and development of the power supply system.